FAKTOR YANG MEMPENGARUHI KESIAPAN MASYARAKAT PESISIR DALAM MELAKUKAN TINDAKAN BANTUAN HIDUP DASAR - Pujianto, Ahmat (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
The prevalence of heart disease in Indonesia in 2018 was reported at 1,017,290 cases. Heart disease can trigger heart attacks and even cardiac arrest. Providing basic life support (BLS) by the bystander can have an impact on the victim's outcome. BLS skills in the public tend to be low, as evidenced by less than 40% of out-of-hospital cardiac arrest victims receiving cardiopulmonary resuscitation (CPR) from the general public, and less than 12% receiving an automated external defibrillator (AED) before the arrival of the ambulance. Other studies also show that less than 1% of the public can perform BLS effectively. This study aims to identify factors that influence the readiness of coastal communities to perform BLS actions. This study is a descriptive-analytical study with a cross-sectional method involving 106 respondents. Data were analyzed using the Kendal Tau test because the data is categorical. The results of the study showed that there was a relationship between knowledge factors and the readiness of coastal communities to perform BLS actions (p = 0.009). There is a relationship between the BHD training factor and the preparedness of coastal communities to perform BHD actions (p = 0.005). There is no relationship between the BHD experience factor and the readiness of coastal communities to perform BHD actions (p = 0.376). The increasing number of emergency conditions in the community, as well as the lack of community knowledge regarding BHD, requires a BHD campaign and training in the community because most emergency conditions occur outside the hospital.